High-temperature Preparation of Ni2P Suspended within Carbon Matrix and its Potential as HER Electrocatalyst - Reinders, Nataliia; Ďurovič, Martin; Honcová, Pavla; Dohnalová, Žaneta; Luxová, Jana; Šlang, Stanislav; Rodriguez Pereira, Jhonatan; Šulcová, Petra (Elsevier Science BV, 2024)
Hydrogen production via electrocatalytic reduction of water is a promising clean-energy technology. For further advancement of this technology, the exploration of cost-effective and streamlined approaches for producing active phosphide-based catalysts is of great importance. This study presents a new high-temperature preparation method of a microporous Ni2P/C catalyst composed of crystalline Ni2P nanoparticles homogeneously distributed within an amorphous carbon matrix in a weight ratio of 40/60. The redox transformation leading to the for-mation of Ni2P from not-reduced stable inorganic salts was facilitated during thermal treatment by a polymeric precursor, which, in turn, transformed into microporous carbon matrix that prevented the newly formed phos-phide particles from agglomerating and sintering. The microporous structure of the prepared composite was characterised by gas adsorption technique and modelled using density functional theory and statistical thickness methods. The t-plot revealed high micropore surface area of 333.5 m(2) g(-1) (accounting 97 % of total surface area) and the pore size distribution in the range of 10-12 angstrom. According to TEM analysis, the size range of the Ni2P inclusions varied from 5 to 200 nm. The evaluation of electrocatalytic properties of the Ni2P/C composite demonstrated its high HER activity and stability under high voltages in alkaline water electrolysis conditions. Furthermore, HER activity of the composite was substantially enhanced by grinding, which opened closed microporosity channels and increased the micropore surface area to 355.2 m(2) g(-1), thereby increasing the number of catalytically active sites in the sample. The result indicates the exceptional role of the microporous micro-structure of the composite in its catalytic performance. The findings of this study may have a significant impact on the practical implementation of efficient hydrogen production by water electrolysis.
Vysokoteplotní příprava Ni2P suspendovaného v uhlíkové matrici a jeho potenciál jako HER elektrokatalyzátor
Keywords: Nickel (II) phosphide; Amorphous carbon matrix; Microporous composite; Polymeric precursor method; Hydrogen production; Fosfid nikelnatý; Amorfní uhlíková matrice; Mikroporézní kompozit; Metoda polymerních prekurzorů; Výroba vodíku